2022
DOI: 10.3390/ijms232315286
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Hub Genes Associated with Psoriasis Using Integrated Bioinformatics Analysis

Abstract: Psoriasis is a chronic, prolonged, and recurrent inflammatory skin disease and the current therapeutics can only alleviate the symptoms rather than cure it completely. Therefore, we aimed to identify the molecular signatures and specific biomarkers of psoriasis to provide novel clues for psoriasis and targeted therapy. In the present study, the Gene Expression Omnibus (GEO) database was used to retrieve three microarray datasets (GSE166388, GSE50790 and GSE42632) and to explore the differentially expressed gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Inhibiting TOPK decreased keratinocytes proliferation and induced keratinocytes apoptosis, and thereby attenuating psoriasis severity. By using integrated bioinformatics analysis, a recent study by Yue et al reported 10 hub genes that may be associated with psoriasis, and TOPK is one of them 37 . However, Yue et al only provided bioinformatic clues for the possible involvement of TOPK in psoriasis, but they did not conduct further experimental studies on TOPK.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting TOPK decreased keratinocytes proliferation and induced keratinocytes apoptosis, and thereby attenuating psoriasis severity. By using integrated bioinformatics analysis, a recent study by Yue et al reported 10 hub genes that may be associated with psoriasis, and TOPK is one of them 37 . However, Yue et al only provided bioinformatic clues for the possible involvement of TOPK in psoriasis, but they did not conduct further experimental studies on TOPK.…”
Section: Discussionmentioning
confidence: 99%
“…[57] It reported that MCM10 expression was higher in the model group than in the blank control group in the TNF-α induced psoriatic HaCaT cell model. [36] On the whole, these genes abovementioned are involved in DNA replication, mismatch repair, cell cycle, and p53 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the expression trends of KRT16, SPRR1A, SPRR1B, and MCM10 were also consistent with previous literature. [33][34][35][36]…”
Section: Isoviolanthin Altered the Transcriptional Gene Expression In...mentioning
confidence: 99%
“…Another miRNA, Mir-129-2-3p, that was found to be associated with psoriasis, was engaged in the malfunctioning of diabetic neutrophils. 11,12 These cytokines and genes contribute to the onset of psoriasis, interfere with insulin signalling, and regulate insulin resistance and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, in transcriptome analysis, many specific genes have revealed the association of psoriasis with MS, such as ACSF2 that is accurate and specific in differentiating psoriasis cases from healthy samples, and impairment of ACSF2 produce is reported to be related to MS and insulin resistance. Another miRNA, Mir‐129‐2‐3p , that was found to be associated with psoriasis, was engaged in the malfunctioning of diabetic neutrophils 11,12 . These cytokines and genes contribute to the onset of psoriasis, interfere with insulin signalling, and regulate insulin resistance and obesity.…”
Section: Introductionmentioning
confidence: 99%